The Fate of Mulatto after Slavery Abolishment as seen in Black Boy by Richard Wright - Zulmardi Abidin (STBA Prayoga Padang, 2016)
Black Boy is a story written by Richard Wright telling about a Mulatto kid, Richard Wright, who struggled for his identity. This story beganfrom his poor parents who lived in Mississippi. Wright had a big problem since he was a kid. He made the final decision to change his life and fateto be better up north. This study analyzed the main character, Richard Wright, his parents and relatives, and his neighbor. This study usesmimetic theory. To analyze this novel, the writer uses qualitative method. The words give big results to the writer to make a descriptive report. Tosupport his study, he used a historical approach to find out what really happened. Fate, Mulatto, slavery abolishment is all about Wright’s life toget his American dream.